The Strategic Decision Making Process behind Outsourcing - Reed, Hannah J (2011)
We have seen a recent rise in the trend towards outsourcing, as it becomes a common strategic decision in many organisations. Drivers behind outsourcing for many organisations focus around cost aspects and the resource based view of the firm, however other components need to be considered when looking at the benefits behind outsourcing. The outsourcing process involves a focus on the decision making exerted by executive decision makers and the role the organisation plays in that process. Current academic literature consists of studies focused around either strategic decision making or outsourcing in organisations. However there seems to be limited literature concerned with combining the two areas together. This paper seeks to do this, creating an in-depth case study of the strategic decision making process behind outsourcing in The University of Nottingham. The main focuses of this study include the decision making process behind outsourcing, the role the University plays in this process and any changing patterns and future trends. Sub areas such as the current literature and the frequency of reviews are also investigated. Interviews were conducted with the management in the University all of whom had significant experience in the outsourcing process. Their knowledge provides us with interesting case examples detailing the outsourcing process. Findings present that there is no one structured process used by all management in the University, who use a variety of different practices to aid them in the process. Despite the rules and regulations instigated by the University as a public organisation there seems to be little political conflict that could potentially ensue from an organisation of political design.